Organik Gübreler: Sürdürülebilirliğin Temeli - Akay, Ayşen; Tohumcu, Faruk; Seferoğlu, Saime; Yeşilyurt, Sevinç; Sertkahya, Mehmet; Doğan, Kemal; Ortaş, İbrahim and Razzaghı, Somayyeh and Tepecik, Mahmut (Academician Publishing Book DOI Portal, 2024)
-